2021
DOI: 10.3389/fpsyg.2021.718315
|View full text |Cite
|
Sign up to set email alerts
|

Technology-Mediated Experiences and Social Context: Relevant Needs in Private Vs. Public Interaction and the Importance of Others for Positive Affect

Abstract: Technologies, such as smartphones or wearables, take a central role in our daily lives. Making their use meaningful and enjoyable requires a better understanding of the prerequisites and underpinnings of positive experiences with such technologies. So far, a focus had been on the users themselves, that is, their individual goals, desires, feelings, and acceptance. However, technology is often used in a social context, observed by others or even used in interaction with others, and thus shapes social dynamics c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Current studies have highlighted the importance of acquiring relevant knowledge on user needs to develop technologies that can handle the real life situations of the older people [ 22 , 23 ]. When developing technological products, it is essential to consider social dynamics and contextual factors [ 24 , 25 ] in order to increase the usability and interaction with technological devices.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have highlighted the importance of acquiring relevant knowledge on user needs to develop technologies that can handle the real life situations of the older people [ 22 , 23 ]. When developing technological products, it is essential to consider social dynamics and contextual factors [ 24 , 25 ] in order to increase the usability and interaction with technological devices.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of the social acceptability of immersive technologies in public spaces is a relatively new topic but there are some initial insights. The current body of work can be divided into research that had a broad look at the social acceptability of new wearable technologies [27,28], or the use of headsets in public [11,22,30,46,72], including more focused work on gaze [3] and gestures [26,32], or discussion of the user and observer roles [4,69,72]. Some authors specifically looked at travelling contexts [5,11,15,65,74,75], but focused on limited application areas, such as entertainment [74], or had a more theoretical approach to the work, lacking in situ studies [15,65] and showed a need for further research in real-world environments [75].…”
Section: Key Challenges Of Using Immersive Technologies In Public Spacesmentioning
confidence: 99%
“…In fact, there are various studies showing that attendants both influence and are influenced by the user (technology interaction). For example, Gentile et al [7] presented some insights on how others present can discourage users of public displays, and Von Terzi et al [8] suggested that formerly public interactions with technology were experienced less positive when imagining the same interaction but without other persons present. Other authors investigated the effects of user interactions on attendants and revealed annoyance (e.g., [9,10]), disturbance (e.g., [11,12]) distraction (e.g., [13,14]), and embarrassment (e.g., [15,16]) as potential consequences.…”
Section: Theoretical Background 21 Attendant Rolementioning
confidence: 99%